A Clinicoimmunohistopathologic Study of Anetoderma: Is Protruding Type More Advanced in Stage Than Indented Type?. (28th December 2016) - Kim, Jung Eun; Sohn, Ki Min; Woo, Young Jun; Jeong, Kwan Ho; Kim, Miri; Lee, Jeong Deuk; Lee, Jun Young; Park, Hyun Jeong; Kim, Gyong Moon; Park, Chul Jong; Yu, Dong Soo; Kang, Hoon
Abstract : Background . The clinical and histopathologic classification of anetoderma are not well characterized. Objective . We aimed to investigate the clinical and histopathologic characteristics of anetoderma and to correlate clinical phenotypes with immunohistopathologic findings. Methods . We retrospectively reviewed the medical records of 30 patients with anetoderma and performed immunohistochemistry for elastin, fibrillin-1, metalloproteinase- (MMP-) 2, MMP-7, MMP-9, and MMP-12, and tissue inhibitor of metalloproteinase- (TIMP-) 1 and TIMP-2. Results . Protruding type ( n = 17) had a longer disease duration and more severe loss of elastin, without changes in fibrillin, than indented type ( n = 13). MMP-2 and MMP-9 showed significantly higher expressions in the dermis compared with controls ( p < 0.05). MMP-7 and MMP-12 showed little expressions in both anetoderma and control tissue. TIMP-1 was highly expressed in anetoderma lesions and controls. TIMP-2 expression was variable. Conclusions . Our findings suggest that protruding type anetoderma may represent a more advanced stage and that MMP-2 and MMP-9 could be responsible for elastic fiber degradation in anetoderma.